Community Desire and Potential for Language Development among the Runga Community of Chad (Impact: Journal of Transformation, 2024)
This paper examines the sociolinguistic situation of the Runga people group in Chad and thepotential for language development in the vernacular language. Sociolinguistic situationrefers to how elements such as region, class, or other languages affect the use of Runga.Language development refers to activities such as creating an orthography, reading materials,and incorporating the language into education or other activities to promote its use. Thispaper affirms the importance of vernacular language development as well as showing thatRunga is still a vital language used by many of the members of the community. Based on asurvey conducted by the author during her master’s research, the expressed desires andopinions of the Runga community are considered and used to come to conclusions about theviability of language development, specifically that orthography development is desired bythe community, as well as incorporating Runga into the educational system. The state ofliteracy and education in the Runga community is considered, as well as examples of otherlanguage development projects among other vernacular languages in Chad that have met withsuccess, such as among the Daza people.